Marketing Strategy To Improve Songket Woven Cloth Business In Sukarara Village (Case Study At Miate Art Shop) - Nendy Pratama Agusfianto (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
This study aims to determine the position of UMKM Miate Art shop in Sukarara Village. The purpose of this study is to determine how to apply the 4P marketing mix (Product, Price, Place, Promotion) and how internal and external factors in the songket woven cloth business at Miate Art Shop, Sukarara Village, Central Lombok Regency. The type of research used is descriptive research. The analytical tool in this study used is SWOT analysis, namely to analyze the internal and external environment of UMKM consisting of strengths, weaknesses, opportunities and threats. After the position of change is known through SWOT analysis, the next step is to find a better marketing strategy to be implemented at UMKM Miate Art Shop. Based on the results of the study shown by the SWOT analysis diagram, it is known that the position of UMKM Miate Art Shop is in quadrant II, which supports a diversification strategy, which means that Miate Art Shop faces various external threats, but still has internal strength. Based on the SWOT analysis, the right marketing strategy that must be used by Miate Art Shop is the ST strategy, namely: Improving the quality of products that are already of good quality to overcome competition with other craftsmen, Maintaining cheap product prices so that they can be reached by consumers, Maintaining existing networks. Keywords: Marketing Strategy, SWOT Analysis